Legions of peace : UN peacekeepers from the global south - Cunliffe, Philip. (Hurst, 2013)
The huge number of security forces stationed around the world as United Nations peace- keepers is second only to the global military deployments of the USA. But most UN peacekeepers come from the emerging powers and developing states that comprise the global South. This is the first book to analyze this phenomenon at the international level.